Implementación de un Sistema de Administración de Red (NMS) para los clientes ISP de la empresa Red Nueva Conexión - Lozano Lozano, Ruben Dario (2023)
Nowadays, knowing the availability of telecommunications equipment is a relevant component, even more so when dealing with Internet Service Providers (ISPs); the company "Red Nueva Conexión" provides technical support and telecommunications consulting services and currently manages the edge network of 35 ISPs, so it must know the problems or inconveniences that arise in the ISP's edge devices, we reported the network problems of these 35 companies through phone calls by the technical staff of each ISP, for which we created a ticket to receive attention later. For this reason, the need arose to implement a Network Management System (NMS) for ISP clients that would allow monitoring and alerting IT personnel of incidents occurring in the 35 ISPs opportunely. To meet this objective, we considered 3 phases. In the first phase, we analyzed three open-source NMS solutions; in the second phase, we configured the Network Management System and agents in the ISP equipment; and in the third phase, we verified the operation of the NMS for the development of this work, we analyzed three Open Source NMS tools, selecting Zabbix as the NMS for its scalability and adaptability; Zabbix monitors 100 Mikrotik devices that make up the infrastructure of the 35 Internet Service Providers (ISPs). For this purpose, we used the Mikrotik SNMP template, consisting of 19 monitoring items and 10 preconfigured triggers that set specific benchmarks to generate alerts indicating severity (high, medium, warning, and informative); we kept track of the devices during June and July by recording 9114 events. The ISPs with the most network problems were Flashnet and Yaneznet, receiving high alerts (60) as "ping unavailable by ICMP" and medium alerts (151) as "Link Down", respectively; we sent these notifications in real-time via email and a Telegram bot configured for communication; allowing network administrators to identify the affected equipment, determine when the problem started and assess its severity; reducing incident detection time and thus improving the attention towards each personalized ISP. Keywords: Open Source, SNMP, monitoring, Zabbix